Meeting European exporting certification standards as a sustainable marketing choice among mango farmers in Ghana - Richard Kwasi Bannor; George Osei; Samuel Kwabena Chaa Kyire (Cogent Economics & Finance, 2023)
Amidst the prevalence of certification and pursuit of global markets, there is a dearth of studies on compliance with EU certification standards and market outlet preference among mango farmers in Ghana. Therefore, this study sought to determine factors influencing mango farmers to produce to meet European standards and certification, and the marketing outlet choice of mango farmers in the Bono and Bono East regions of Ghana. A multistage sampling technique was employed to select 300 mango farmers. Data gathered were analysed using multinomial and binary probit regressions. Empirical results show that gender, age, farming experience, and access to the ready market are significant predictors of a farmer's choice of the local market. On the other hand, farming experience, ready market, the quantity of harvest, fruit quality, market assurance, and good agronomic practices (GAP) significantly predict farmers' preference for retail. The level of education, farm size, GAP, annual farm income, ready market, training, and access to credit are essential determinants of a farmer's decision to practise EU standards and certification. Given the findings, it is recommended that farmers who sell and are likely to sell to processors should be targeted for pieces of training on EU market export as they are more likely to be convinced and already involved in relevant practices for such exports
Keywords: 330; certification; European standards; good agricultural practices; mango; marketing